Pemenuhan Hak Pekerja Berupa BPJS Ketenagakerjaan Dan Subsidi Upah Covid-19 (Studi Kasus CV. Raphita Muda Berkarya) - Sinaga, Theresia; Lestari, Rika; Hendra, Rahmad (Peneliti.net, 2024)
CV. Raphita Muda Berkarya, where there are four of its twelve workers, is known to have not been registered in the BPJS Employment program. The non-registration of each worker as a participant in the BPJS Employment program has harmed each individual worker because they do not get what they are entitled to as workers if in the future there is a work accident or unwanted things. This makes labor rights not fulfilled to the maximum. This situation is further exacerbated by the outbreak of the Covid-19 pandemic which has a major impact on Furthermore, this study aims to determine the fulfillment of BPJS Employment rights to workers and the efforts taken by workers. This research will be structured using the type of empirical juridical research, namely analyzing a problem that is correlated or connected with the current laws and regulations. This research is descriptive in nature to provide symptoms, facts or events in a systematic and accurate manner, regarding the nature of a particular population. The data sources used consist of primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques in this study were carried out by interviews and literature review by taking quotations from the literature that are related to the problem being studied. The results of this study are first, it is known that the implementation of salary or wage subsidy assistance for CV workers. Raphita Muda Berkarya has not run according to the regulations stipulated in Law Number 24 of 2011 concerning the Social Security Organizing Agency, so that some workers do not get their rights to get COVID-19 wage / salary subsidy assistance, both workers can take several efforts such as, carrying out the obligation to register personal data with the company and asking for responsibility in the form of losses to their workers due to companies that do not register workers as BPJS Employment participants.